2018
DOI: 10.1021/acsomega.8b02161
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein: An Aggressive Scavenger—The Metabolism of Rhodium(II) Tetraacetate (Rh2(CH3CO2)4)

Abstract: Anthropogenic sources of xenobiotic metals with no physiological benefit are increasingly prevalent in the environment. The platinum group metals (Pd, Pt, Rh, Ru, Os, and Ir) are found in marine and plant species near urban sources, and are known to bioaccumulate, introducing these metals into the human food chain. Many of these metals are also being used in innovative cancer therapy, which leads to a direct source of exposure for humans. This paper aims to further our understanding of nontraditional metal met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 110 publications
0
12
0
Order By: Relevance
“…In solution studies demonstrated that dirhodium carboxylate compounds are able to bind proteins [ 12 , 22 , 23 , 26 , 28 , 29 ]. However, there are only very scarce structural information on this interaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In solution studies demonstrated that dirhodium carboxylate compounds are able to bind proteins [ 12 , 22 , 23 , 26 , 28 , 29 ]. However, there are only very scarce structural information on this interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their possible role in the definition of the mechanism of action of these potential anticancer agents, the interactions of [Rh 2 (μ-O 2 CCH 3 ) 4 ] with amino acids, peptides, and proteins have been studied, but contrasting results have been reported in the literature [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Reaction of [Rh 2 (μ-O 2 CCH 3 ) 4 ] with Cys and its derivatives and with glutathione leads to oxidation of the Rh(II)–Rh(II) dimeric unit and formation of Rh(III)–Rh(III)-containing dimeric and oligomeric species [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analogous compounds were found to be effective against Ehrlich ascites 2-4, 15-17 , L1210 tumors [6][7] , sarcoma 180 and P388 leukemia 18 , but the appearance of severe toxic side effects prevented their further evaluation. Although the origin of the antitumor activity of dirhodium carboxylates is not known, plausible cellular targets are single-stranded and double stranded DNA 18 , amino acids [19][20] , peptides [21][22] and proteins [23][24][25][26][27][28][29] . In this frame, though several studies on the interactions of [Rh2(µ-O2CCH3)4] with peptides and proteins have been reported in the literature [23][24][25][26][27][28][29] , the mode of binding of the dirhodium center to proteins has not been elucidated yet.…”
Section: Introductionmentioning
confidence: 99%
“…The dirhodium tetraacetate complex [Rh 2 (μ-O 2 CCH 3 ) 4 ] includes a Rh­(II)–Rh­(II) bond with four carboxylates playing the role of bridging ligands arranged in a lantern-like form around the central bimetal unit, whereas neutral solvent molecules (L) occupy the axial coordination sites. Although causing toxic side effects, this complex has a proven activity against several cancer types, such as sarcoma 180, P388 leukemia, L1210 tumors, and Ehrlich-Lettre ascites carcinoma. Nevertheless, its mode of action is not yet disentangled despite several studies on its interaction with various proteins, although it is hypothesized that its biomolecular targets are single- and double-stranded DNA, proteins, peptides, , and amino acids. Moreover, interaction of dirhodium compounds with peptides and proteins was investigated in the framework of protein modification with the aim of designing artificial metalloenzymes. , Usually, Rh-based complexes are coordinated to proteins either via the covalent linkage, involving direct binding of these metal complexes to proteins, , or via the dative anchoring which is based on the formation of noncovalent interactions between protein atoms and Rh ligands as well as coordinative bonds between protein side chains and Rh centers . There are experimental pieces of evidence of the Rh-complex selectivity toward side chains of Asn, Asp, His, Lys, and the C-terminal carboxylate. ,, …”
Section: Introductionmentioning
confidence: 99%